A model for the promotion of consumption of locally available indigenous vegetables among primary school children - Mbhatsani, Hlekani Vanessa; Tambe, Betrand Ayuk; Zuma, Mthokozisi Kwazi; Mbhenyane, Xikombiso G. (Frontiers in Nutrition, 2024)
The study's primary aim was to develop a model for promoting the consumption of selected locally available indigenous vegetables for primary school children. Model development was phase three of a bigger study. A qualitative approach was used for this phase. The model was developed following three steps: model design, development, and validation. The iterative phases of model development starting with data preparation, data understanding, model assembly, model audit and model delivery were adopted. The model is influenced by the World Health Organization's approaches (medical, educational, behavioural change, empowerment, and societal change approaches). The researchers synthesised the data from phases one and two of the study and selected content which suited the model. Two experts' engagement consultations were conducted for inputs: one face-to-face and one virtual. This was followed by model validation from the end users. The model developed for this study proposes that, for the promotion of locally available indigenous vegetables within the primary school setting, the following critical issues should happen: i) a medical approach should be in place; ii) education or correct information should be provided; iii) behavioural change should be enabled; iv) empowerment should be provided, and v) societal enhancement should be encouraged. Furthermore, it suggests that the promotion of the consumption of locally available vegetables among primary school children can be achieved when the identified stakeholders work together.